Manajemen Kurikulum Terpadudi Pondok Pesantren Modern Ummul Quro Al-Islami Bogor - Agus Ali; Nurwadjah Ahmad EQ ; Andewi Suhartini (Jurnal Dirosah Islamiyah, 2022)
This article aims to discuss integrated curriculum management at the modern Islamic boarding school Ummul Quro Al-Islami Bogor, including: planning and implementing an integrated curriculum. By using a descriptive qualitative method, Based on the results of research on integrated curriculum management at the Modern Islamic Boarding School Ummul Quro Al-Islami, it can be concluded as follows: (1) Integrated curriculum planning consists of, intra-curricular, co-curricular and extracurricular, integrated curriculum planning include: (1) goals, (2) programs, (3) schedule of activities. Educational programs include; Faith, Islam, Akhlaq Karimah, Science, Citizenship / Nationality, Art and Beauty (Aesthetics), Entrepreneurship and Technical Skills, Da'wah and Society (Khidmah al-Ijtimaiyyah), Leadership and Management, Teacher Training, Islamic Boarding School, Physical Education and Health, Scouting Tahfidzul Qur'an. Santri live in disciplined dormitories for 24 hours under the guidance of teachers and Kyai, the activity schedule consists of Daily, Weekly, Semester and Yearly. (2) The organization of the curriculum that applies at the Modern Islamic Boarding School Ummul Quro Al-Islami is a combination of the pesantren education curriculum and the government curriculum (Ministry of Religion), so that graduates can continue to higher education levels, both at home and abroad. Modern Islamic Boarding School Ummul Quro Al-Islami is a level of education for 6 (six) years and 4 (four) years, 6 years namely, I, II and III which are equivalent to classes I, II, III SMP and classes IV, V and VI which equivalent to class I, II and III MA and 4 years, namely one year of intensive Arabic and English language training using an integrated curriculum. Keyword: Management, Integrated Curriculum And Modern Pesantren